The use of AI in the fashion industry : the impacts on intellectual property rights - Briote, Sara de Freitas Pessoa (2023)
The fashion industry is constantly evolving and adapting to new technologies. Artificial Intelligence (AI) is one of the most transformative and disruptive technologies that are being adopted by the fashion industry as it can be used to create designs, and patterns, analyse consumer data, and help customer services. With the increasing use of AI in the fashion industry, important legal questions arise, especially in terms of intellectual property (IP). Therefore, understanding how AI impacts intellectual property rights is important as AI tools are disrupting some central concepts in IP law. This master thesis will explore the impact of AI-generated outputs on the different IP rights, namely copyright, patents, designs, trademarks, and trade secrets, as well as the challenges and strategies for protecting AI-generated outputs in the fashion industry. Considering the impact of AI on IP rights, this master thesis aims to analyse the different legal questions that are emerging from AI-generated outputs, and which are being objects of discussion by the IP community, regarding copyright, patents, designs, trademarks, and trade secrets. In particular, in this thesis we are going to explore the challenges of protecting AI generated outputs within the current European legal frameworks, namely, we will examine each requirement for protection under each European legal IP right system using for this purpose literature, legislation, and case studies. Moreover, we intend to point out these issues because AI can be helpful and be seen an opportunity for fashion brands, but they also can lead to legal conflictive situations.